EFEK PROBIOTIK TERHADAP PENINGKATAN BERAT BADAN AYAM PEDAGING - Damai Kusumaningrum (Politeknik Pertanian Negeri Kupang, 2009)
This aim of research was to know the effect of probiotics for body weight of broiler. Thirty six Daily Old Chick of broiler, strain Arbor acress, male sex were divided to become 2 group: I ( given standard food) and II ( given standard food + probiotics) with 18 chicken of each group. Probiotics were given at the age of 8 days by sprayed in food with the dose 2 ml / 250 ml water / 1 kg food. The body weight was observed for all group at the age of 8, 15, 22, and 39 days. The data of body weight were analyzed with Split plot method.The result showed that the body weight increased of group I and II was not significantly difference (P > 0,05), period I and III, II and III was significantly difference (P < 0,05). The conclusion was probiotics does not effective for body weight.Keywords: probiotic, body weight